Pengaruh Pertumbuhan Ekonomi, Pendidikan Dan Pengangguran Terhadap Ketimpangan Distribusi Di Jawa Tengah Tahun 2020-2024 - Moh Alif Febriyan; Maulidyah Indira Hasmarini (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the impact of economic growth, education, and the open unemployment rate on income distribution inequality in Central Java from 2020 to 2024. The method used is panel data regression with an econometric approach, utilizing time-series data from 2020 to 2024 and cross-section data from 35 regencies/cities in Central Java. The regression model applied includes three main approaches: the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), with specification tests to determine the best model. The results indicate that Gross Regional Domestic Product (GRDP) significantly affects income distribution inequality, whereas education and the open unemployment rate have no significant influence.